Instrumental Estimation of E-Model Parameters for Wideband Speech Codecs. (5th October 2010) - Möller, Sebastian; Côté, Nicolas; Gautier-Turbin, Valérie; Kitawaki, Nobuhiko; Takahashi, Akira
Abstract : A method is described for quantifying the quality of wideband speech codecs. Two parameters are derived from signal-based speech quality model estimations: (i) a wideband equipment impairment factorI e, WB and (ii) a wideband packet-loss robustness factorB pl, WB . The equipment impairment factor can be combined with impairment factors for other quality degradations to form an estimate of the overall conversational qualityR of a wideband communication scenario, using a wideband extension of the E-model. The packet-loss robustness factor captures the robustness of the codec against packet-loss degradations. In contrast to past work, these parameters are no longer determined on the basis of auditory test results, but from signal-based speech quality models. We applied three intrusive models to several databases and compared the derived quality estimates and impairment factors to those obtained from auditory tests. The results show that when migrating from narrowband to wideband transmission—a quality improvement of roughly 30% can be obtained, which is very similar to the one observed in auditory tests. The estimated impairment factors show a high correlation to those derived from auditory scores. Congruences and discrepancies to auditory test results are discussed, and an outline of work necessary to set up a wideband or even superwideband E-model is given.